Distribution Nature of Trade Volume and Number of Trades at NEPSE Floor - Vaidya, Rashesh; Sharma, Dilli Raj; Dangol, Jeetendra (Saptagandaki Journal, 2022)
Investors are concerned with market fluctuation. At NEPSE, market fluctuation is linked to the trade volume and number of shares traded during a specific day. A change in the benchmark index, NEPSE, in the Nepalese stock market depends on the market capitalization. Hence, to estimate the market pattern, a better understanding of the distribution nature of the trade volume and number of trades is beneficial to Nepalese investors. This ultimately helps an investor understand the market mechanism. The paper has followed basic descriptive statistics and a graphical presentation of the PP Plot, QQ Plot, and PDF Plot to test the normality and distribution nature of the NEPSE yearly trade volume and number of trades. Finally, the Sharpio-Wilk test, Jarque-Bera test, Kolmogorov-Smirnov test, and Anderson-Darling (A2) test are applied to test the goodness of fit for the observed and the respective NEPSE yearly trade volume and number of trades. The paper found that the NEPSE's yearly trade volume and number of trades from the year of its establishment to the fiscal year 2021–22 have a leptokurtic distribution. Similarly, the paper shows the distribution of trade volume and the number of trades toward non-normality. The probability distribution function reflects the log-normal (3P) distribution, also known as Galton’s distribution, for both sets of data. The distribution of the NEPSE's yearly trade volume and number of trades is best fitted by Galton’s distribution. The fitting of this specific distribution reflects a compounding effect on the transactions taped during the last two decades and more . Hence, an investor who enters in a NEPSE floor with a small numbers of scrips would multiply the numbers in a period of times.